Adaptation to developmental diet influences the response to selection on age at reproduction in the fruit fly. (27th February 2019) - May, Christina M.; van den Heuvel, Joost; Doroszuk, Agnieszka; Hoedjes, Katja M.; Flatt, Thomas; Zwaan, Bas J.
Abstract: Experimental evolution (EE) is a powerful tool for addressing how environmental factors influence life‐history evolution. While in nature different selection pressures experienced across the lifespan shape life histories, EE studies typically apply selection pressures one at a time. Here, we assess the consequences of adaptation to three different developmental diets in combination with classical selection for early or late reproduction in the fruit fly Drosophila melanogaster . We find that the response to each selection pressure is similar to that observed when they are applied independently, but the overall magnitude of the response depends on the selection regime experienced in the other life stage. For example, adaptation to increased age at reproduction increased lifespan across all diets; however, the extent of the increase was dependent on the dietary selection regime. Similarly, adaptation to a lower calorie developmental diet led to faster development and decreased adult weight, but the magnitude of the response was dependent on the age‐at‐reproduction selection regime. Given that multiple selection pressures are prevalent in nature, our findings suggest that trade‐offs should be considered not only among traits within an organism, but also among adaptive responses to different—sometimes conflicting—selection pressures, including across life stages.